2014
DOI: 10.3109/15622975.2013.842654
|View full text |Cite
|
Sign up to set email alerts
|

Extended release quetiapine fumarate as adjunct to antidepressant therapy in patients with major depressive disorder: pooled analyses of data in patients with anxious depression versus low levels of anxiety at baseline

Abstract: Adjunct quetiapine XR demonstrates efficacy in patients with anxious and non-anxious depression, assessed using HAM-A total score, and anxious depression assessed using HAM-D anxiety/somatisation factor score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Although monotherapy with antidepressant treatments (ADTs) can be effective in treating MDD with anxiety symptoms, patients may be less likely to experience sustained response or remission (Ionescu et al., ). Subgroup analyses of short‐term, larger studies have indicated that augmentation with an antipsychotic is an effective strategy in the treatment of MDD with anxiety symptoms (Bandelow et al., ; Trivedi et al., ). Pooled analysis from two double‐blind, placebo‐controlled studies in patients with MDD and inadequate response to ADTs demonstrated that augmentation with aripiprazole improved Montgomery–Åsberg Depression Rating Scale (MADRS) total score in a subgroup with baseline Hamilton Rating Scale for Depression (HAM‐D) anxiety/somatization factor score ≥ 7 (Trivedi et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although monotherapy with antidepressant treatments (ADTs) can be effective in treating MDD with anxiety symptoms, patients may be less likely to experience sustained response or remission (Ionescu et al., ). Subgroup analyses of short‐term, larger studies have indicated that augmentation with an antipsychotic is an effective strategy in the treatment of MDD with anxiety symptoms (Bandelow et al., ; Trivedi et al., ). Pooled analysis from two double‐blind, placebo‐controlled studies in patients with MDD and inadequate response to ADTs demonstrated that augmentation with aripiprazole improved Montgomery–Åsberg Depression Rating Scale (MADRS) total score in a subgroup with baseline Hamilton Rating Scale for Depression (HAM‐D) anxiety/somatization factor score ≥ 7 (Trivedi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Pooled analysis from two double‐blind, placebo‐controlled studies in patients with MDD and inadequate response to ADTs demonstrated that augmentation with aripiprazole improved Montgomery–Åsberg Depression Rating Scale (MADRS) total score in a subgroup with baseline Hamilton Rating Scale for Depression (HAM‐D) anxiety/somatization factor score ≥ 7 (Trivedi et al., ). Quetiapine extended‐release (XR) augmentation has also been reported to improve MADRS total score in subgroups of patients with MDD and inadequate response to ADTs, with anxious depression defined as baseline HAM‐D anxiety/somatization factor score ≥ 7, and alternatively as baseline Hamilton Rating Scale for Anxiety (HAM‐A) ≥ 20 (Bandelow et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, pooled data from two adjunctive quetiapine trials did find significant antidepressant efficacy for quetiapine versus placebo in patients with anxious depression (with a mean difference in reduction in Montgomery-Asberg Depression Rating Scale (MADRS) scores in patients treated with 150mg or 300mg of adjunctive quetiapine versus placebo of 2.6 and 3.3, respectively). (Bandelow et al, 2014) Interestingly enough, however, equivalent differences in efficacy for patients with low levels of anxiety in those two trials were not in the clinically significant range (1.7 versus 1.2 for 150mg and 300mg, respectively). Equivalent differences in changes in HAM-A scores for these two populations were 1.65 and 2.03 (in favor of quetiapine 150mg and 300mg, respectively, p <0.05) versus 1 and 0.8 (in favor of quetiapine 150mg and 300mg, respectively, p >0.05).…”
Section: Discussionmentioning
confidence: 90%
“…Studies focussing on clinical or biological characteristics of subtypes of depression most often compared one subtype of depression with patients not exhibiting this subtype (Bandelow et al, ; Baune et al, ; Harkness & Monroe, ; Kaestner et al, ; Liu et al, ; Monzon et al, ; Papakostas, Fan, & Tedeschini, ; Paslakis et al, ; Pizzagalli et al, ; Quinn, Rennie, Harris, & Kemp, ; Seppala et al, ; Zaninotto et al, ). However, such approaches do not account for the underlying heterogeneity, since other subtypes were disregarded in dichotomous approaches.…”
Section: Introductionmentioning
confidence: 99%